ILMI URDU LUGHAT (JAAMAY) AND PRINCIPLES OF LEXICOGRAPHY: (lexical entries, Order of lexicalentries and orthography) - Nasir Mahmood Ahmad; Dr. Safdar Rashid (Zaban-o-Adab, 2022)
Waris Sirhandi is one of the leading Urdu lexicographers of Pakistan. In this field he has many things on his credit, the most important of these is ‘Ilmi Urdu Lughat (Jaamay). He has also done critical reviews of many important Urdu dictionaries. The present research article is an analytical study of this import work. The study has been made keeping in view the principles of lexicography like: entry word, order of lexical entries, old and new way of orthography. The article also tries to judge the lexicon in the light of the principles and claims set by the compiler himself.